SPIM workflow manager for HPC - Kožusznik, Jan; Bainar, Petr; Klímová, Jana; Krumnikl, Michal; Moravec, Pavel; Svatoň, Václav; Tomančák, Pavel (Bioinformatics, 2019)
SUMMARY: Here we introduce a Fiji plugin utilizing the HPC-as-a-Service concept, significantly mitigating the challenges life scientists face when delegating complex data-intensive processing workflows to HPC clusters. We demonstrate on a common Selective Plane Illumination Microscopy image processing task that execution of a Fiji workflow on a remote supercomputer leads to improved turnaround time despite the data transfer overhead. The plugin allows the end users to conveniently transfer image data to remote HPC resources, manage pipeline jobs and visualize processed results directly from the Fiji graphical user interface. AVAILABILITY AND IMPLEMENTATION: The code is distributed free and open source under the MIT license. Source code: https://github.com/fiji-hpc/hpc-workflow-manager/, documentation: https://imagej.net/SPIM_Workflow_Manager_For_HPC. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Software; software; Microscopy; Workflow; průběh práce; mikroskopie; počítačové zpracování obrazu; Image Processing, Computer-Assisted